Determination of Thermal Properties of Autoclaved Aerated Concrete Wall Sections Constructed with Distinct Mortars by the Experimental and Theoretical Data - Koçkar Tuğla, Rukiye; Örgel, Orhan Emre (Firat Universitesi, 2024)
This study investigated the thermal properties of autoclaved aerated concrete(AAC) wall sections constructed with distinct mortars. Within the scope of the study, four distinct wall sections of 25x25x5cm dimensions were created using AAC special adhesive mortar, cement mortar, lime mortar and cement-lime mortar. The thermal conductivity(λEXP) that was determined by the heat flow meter(HFM) method and bulk density(ρEXP) of each wall section was determined in the laboratory. Specific heat values(cEXP) of mortars and aerated concrete material were determined experimentally in the study. The thermal diffusivity value(αEXP), thermal effusivity value(eEXP) and volumetric heat capacity(VHCEXP) of each wall sample were calculated using the experimental data obtained in the laboratory. In addition, αTEO, eTEO and VHCTEO of each wall sample were calculated theoretically using the thermal conductivity, bulk density and specific heat value given in the literature and standards for the same wall sections. In the study, experimental data was compared to the theoretical data. As a result, the thermal properties of walls constructed with distinct mortars and thermal differences formed in the walls due to the effect of these mortars could be determined with experimental data. However, it was observed that theoretical data were insufficient to detect these thermal differences.
Keywords: Construction Materials; Yapı Malzemeleri; Autoclaved aerated concrete wall; thermal conductivity; specific heat value; thermal diffusivity; thermal effusivity; Gaz beton duvar; ısıl iletkenlik hesap değeri; özgül ısı değeri; ısıl yayınırlık; ısıl dağınırlık